An efficient adaptive frequency sampling scheme for large-scale transient boundary element analysis. (15th April 2016) - Xiao, Jinyou; Rong, Junjie; Ye, Wenjing; Zhang, Chuanzeng
Highlights: Aims at reducing the computational cost for BEM transient analysis using the frequency-domain approach. Proposes an adaptive algorithm to determine the optimal sampling frequencies. Achieves 2 to 4 times reduction of the total computational cost. Abstract: The frequency-domain approach (FDA) to transient analysis of the boundary element method, although is appealing for engineering applications, is computationally expensive. This paper proposes a novel adaptive frequency sampling (AFS) algorithm to reduce the computational time of the FDA by effectively reducing the number N c of sampling frequencies. The AFS starts with a few initial frequencies and automatically determines the subsequent sampling frequencies. It can reduce N c by more than 2 times while still preserving good accuracy. In a porous solid model with around 0.3 million unknowns, 4 times reduction of N c and the total computational time is successfully achieved.